2014
DOI: 10.5901/ajis.2014.v3n6p501
|View full text |Cite
|
Sign up to set email alerts
|

Building a Solid Health Care System in Nigeria: Challenges and Prospects

Abstract: The most significant ingredient of life is health. No wonder the oft-spoken slogan: "Health is wealth", has remained evergreen in our memory. This is why inasmuch as life is the greatest gift of God to man, the provision of health care facilities is needed in superfluity in order that life may be sustained on earth. Unfortunately, in Nigeria today, the provision of health care facilities seems to be at low ebb as many Nigerian are vulnerably exposed to the danger of death. This situation gives the ugly impress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…In the study by Uzochukwu and Unwujekwe [31], it was found that at the initial point when the user-fees was introduced along with the Drug Revolving Fund (DRF), there was significant improvement in medicines availability and improvement in health services; however, as the health workers became de-motivated and involved in selling their own drugs for their own profit, the policy failed. Thus, the present finding that an overwhelming proportion of study participants usually do not find their prescribed medicines in the hospitals, only buttresses the notion that Nigerian hospitals are in a decayed state and nothing more than consulting clinics [32, 33]. Nigerian hospitals are referred to as mere consulting clinics because both “free drugs” (as practiced in some states in Nigeria) and even the essential medicines are not available, thus, making the care of common ailments difficult [33].…”
Section: Discussionmentioning
confidence: 62%
“…In the study by Uzochukwu and Unwujekwe [31], it was found that at the initial point when the user-fees was introduced along with the Drug Revolving Fund (DRF), there was significant improvement in medicines availability and improvement in health services; however, as the health workers became de-motivated and involved in selling their own drugs for their own profit, the policy failed. Thus, the present finding that an overwhelming proportion of study participants usually do not find their prescribed medicines in the hospitals, only buttresses the notion that Nigerian hospitals are in a decayed state and nothing more than consulting clinics [32, 33]. Nigerian hospitals are referred to as mere consulting clinics because both “free drugs” (as practiced in some states in Nigeria) and even the essential medicines are not available, thus, making the care of common ailments difficult [33].…”
Section: Discussionmentioning
confidence: 62%
“…There is an absence of clarity of roles among the tiers of government who are responsible for the poor state of the health sector in Nigeria [18].…”
Section: A the Nigerian Health Care System And The Classifications Of Hospitals In Nigeriamentioning
confidence: 99%
“…These classified organizations of the health system should allow the effective functioning of the health system, but the performance of the Nigerian health sector is still described as poor. There is an absence of clarity of roles among the tiers of government who are responsible for the poor state of the health sector in Nigeria [ 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The federal government has no say in how states utilize their allocations, and cannot mandate them to spend a certain amount on healthcare, making it difficult to gauge the effectiveness of any campaign for improvement on a cohesive nation-wide level. Consider that the Federal Ministry of health usually spends about 70% of its budget in urban areas where only a shabby 30% of the population resides, what an existential irony (Innocent, 2014).…”
Section: Challenges and Prospects Of The Nigerian Health Sectormentioning
confidence: 99%